Ultrasound-induced mechanical damage of cancer cell cytoskeleton causes disruption of nuclear envelope and activation of cGAS-STING - Giorgia Federico; Angelo Rosario Carotenuto; Arsenio Cutolo; Stefania Palumbo; Marialuisa Moccia; Simona Paladino; Massimo Santoro; Tommaso Russo; Massimiliano Fraldi; Francesca Carlomagno (Scientific Reports)
Abstract Neoplastic transformation is accompanied by critical changes in cell mechanical properties, including reduced cell elasticity. By leveraging such mechanical flaw, exposure to low intensity therapeutic ultrasounds (LITUS) has been proposed as a tool for selective killing of cancer cells. Here, we have developed dynamic models to address the morpho-mechanical differences between prostate cancer and non-tumoral counterparts and studied the effects of LITUS on cell viability. We show that LITUS exposure (1 MHz) leads to cancer-selective cytoskeletal disruption associated to loss of nuclear envelope integrity, DNA damage marked by γH2AX and 53BP1 foci, and release of DNA into the cytosol with activation of the cGAS–STING signaling cascade. Mechanistically, the LINC complex, which connects the cytoskeleton to nucleoskeleton and chromosomes, is critical to mediate nuclear rupture triggered by LITUS. Accordingly, genetic ablation of the LINC component SUN2 tuned down DNA damage and cGAS–STING signaling while the inactivation of the endosomal sorting complex (ESCRT), required for the transport machinery that preserves the nuclear envelope integrity, enhanced cell killing by LITUS. In conclusion, LITUS induce cancer cell DNA damage and an innate immune response, this suggesting LITUS treatment as a mechanobiology-driven anti-neoplastic strategy.